Factors Affecting Capital Structure And Stock Prices Of Agricultural And Mining Companies - Gracia, Ivena; Panggabean, Rosinta Ria (Kesatuan Press, 2019)
The purpose of this study was to analyze the influence of business risk, asset growth, sales growth, earning per share, and asset structure to capital structure and share price. This study involved mining and agriculture companies listed on IDX within the period of 2010-2017. The analysis employed eViews 9. Based on the hypothesis testing, it was found that that business risk, sales growth, and asset structure do not have a significant effect on capital structure. However, asset growth has a significant influence. Furthermore, sales growth and EPS do not have a significant effect on share price, but the asset structure has a significant influence. This research is a development of previous research by adding earnings per share as an independent variable and covering the period 2010 - 2017 in order to show the most actual conditions. Company management can make the results of this study a consideration in determining the optimal capital structure. This study only examined the mining and agricultural sectors on the Indonesian stock exchange.